Price Discrimination in Aviation: The End of the Loyalty to the National Carrier - Frank Bruinsma; Piet Rietveld; Ricardo Westra (European Regional Science Association (ERSA), 2003)
In this study differences in airfares between citypairs will be analysed. We distinguish three types of city pairs: pairs within western Europe, pairs within eastern Europe and pairs between western and eastern European cities. In this study the differences in airfares of the national carriers are analysed. For instance, the fares of KLM and Lufthanse for the city pair Amsterdam - Berlin, in both directions. The fares are analysed for both economy and business class travellers. Explanations in differences are, amongst others, sought in the differences in income level, other competing airlines, the loyalty to the own national carrier, et cetera.
Keywords: 330